Beyond one term of mentoring: A new approach to the research mentorship of undergraduate students - Julius Kitutu; Maura McCall; Rebecca Findle; Khadejah F. Mahmoud; W. Brian Greene (Elsevier, 2016)
Background: The Undergraduate Research Mentorship Program (URMP) at the University of Pittsburgh (UPitt), School of Nursing (SoN) was envisioned and implemented in the 2008-2009 academic year to expose undergraduate students to research early in their college educational experiences. Moreover, the URMP is a method to retain current students and attract new high school applicants to the SoN. Methods: This article presents (1) the program's conceptualization, objectives, implementation, and outcomes using descriptive statistics and (2) the strengths of the URMP as well as the opportunities gained and lessons learned through conducting the program. Results: The program has shown success in attracting students to get involved in research. To date, 63.3%-75.7% of participating students reported gaining various research skills from the URMP. Additionally, URMP students have reported participating in conferences and creating close relationships with their mentors; indeed, 97% of these students are interested in pursuing a graduate education. Moreover, the majority of URMP student participants (85.7%) have reported that not only the research experience met or exceeded their expectations, but also they were very satisfied with the research experience. Conclusion: Through the URMP, unlike a traditional didactic class, students can benefit from experiential learning, incentives to participate, and a mentoring relationship without the added pressure of obtaining grades at the end of the term. Keywords: Mentorship, Research, Nursing, Undergraduate, Education